Predictors of unplanned drinking in daily life: The influence of context, impulsivity, and craving in those with emotion dysregulation - Griffin, Sarah A. (Addict Behav, 2021)
OBJECTIVE: Unplanned drinking, or drinking that violates intentions, has been linked to significant alcohol-related consequences; however, little is known about what factors within individuals’ daily lives predict whether unplanned drinking occurs. This study examines the influence of daily-life impulsivity, alcohol craving, and interpersonal contexts on unplanned drinking. METHOD: Ecological Momentary Assessment (EMA) data were collected from 32 moderate drinkers. Participants were prompted six times per day for up to 21 days. Each morning participants reported whether they planned to drink that day. Multilevel and GEE models predicted drinking behaviors on days without intent to drink from daily-life interpersonal contexts, and pre-drinking ratings of impulsivity and craving. RESULTS: Spending time in a bar and spending relatively more time with other people on days with no intention to drink was associated with drinking. Individuals who experienced higher craving prior to drinking were relatively more likely to engage in unplanned drinking. When participants reported relatively greater difficulties with premeditation, they were more likely to subsequently report initiating an unplanned drinking episode. Results also suggest that individuals generally higher on negative urgency may be less likely to engage in unplanned drinking but drink more when they do. CONCLUSION: These results indicate the influence of daily-life contexts, craving, and impulsivity on unplanned drinking behavior. We highlight several possible avenues for intervention and prevention efforts including modifying social and interpersonal environments, screening for craving patterns, and targeting cognitive deficits in planning.